The Role of Renal Macrophage, AIM, and TGF-β1 Expression in Renal Fibrosis Progression in IgAN Patients - Yang, Min; Liu, Jia Wei; Zhang, Yu Ting; Wu, Gang (Frontiers in Immunology, 2021)
Objective: To analyze the expression of macrophages, AIM, TGF-β1 in the kidney of IgAN patients, and to explore the role of macrophages, AIM, TGF-β1 in the progression of renal fibrosis in IgAN patients. Methods: The paraffin specimens of renal tissue from 40 IgAN patients were selected as the observation group. At the same time, paraffin specimens of normal renal tissue from 11 patients treated by nephrectomy were selected as the normal control group. We observed the distribution of macrophages, the expression of AIM and TGF-β1 by immunohistochemical staining and/or immunofluorescence. Result: The number of M0, M1, M2 macrophages could be found increased in IgAN patients. M0 macrophages are mainly polarized towards M2 macrophages. The expression of AIM and TGF-β1 were significantly higher in IgAN patients than in NC. M2 macrophage, AIM and TGF-β1 were positively correlated with serum creatinine and 24-hour proteinuria, but negatively correlated with eGFR. M2 macrophages, AIM, TGF-β1 were positively correlated with fibrotic area. Conclusion: M2 macrophages, AIM and TGF-β1 play important roles in the process of IgAN fibrosis, and the three influence each other.